2011
DOI: 10.1118/1.3602457
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary nodule registration: Rigid or nonrigid?

Abstract: Purpose: The primary aim of this study is to investigate the performance difference of rigid and nonrigid registration schemes in matching corresponding pulmonary nodules depicted on sequential chest computed tomography (CT) examinations. Methods: A gradient descent based rigid registration algorithm with scaling was developed and it handled the involved geometric transformations (i.e., translation, rescaling, shearing, and rotation) separately instead of optimizing them in a single pass. Given two lung CT exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…However, it should be noted that it is quite challenging to perform deformable registration of the initial tumor volume on planning CT to a significantly different or even nonexistent tumor volume on the follow-up CT. Observed differences in lung density were, in part, likely due to suboptimal coregistration of planning and follow-up CT scans, although rigid registration was shown to be a simpler, yet valid approach in a study by Gu et al in the context of follow-up examinations for lung nodules [64].…”
Section: Ctcae Rp Gradementioning
confidence: 99%
“…However, it should be noted that it is quite challenging to perform deformable registration of the initial tumor volume on planning CT to a significantly different or even nonexistent tumor volume on the follow-up CT. Observed differences in lung density were, in part, likely due to suboptimal coregistration of planning and follow-up CT scans, although rigid registration was shown to be a simpler, yet valid approach in a study by Gu et al in the context of follow-up examinations for lung nodules [64].…”
Section: Ctcae Rp Gradementioning
confidence: 99%
“…Some investigators have argued that, due to respiratory motion causing either inflation or deflation of the lung parenchyma, DR should be utilized when comparing CT scans. 38,39 However, in a series examining different registration algorithms for 60 pulmonary nodules compared to follow-up scans at an average of 2 years followup, Gu et al showed that rigid registration (RR) had equivalent accuracy compared with DR. 40 In their series, Diot et al found discrepancies of <5% for doses less than 60 Gy in a subset of their patients when comparing DR and RR. 17 We performed a subset analysis using DR in 23 patients for geometric modeling purposes.…”
Section: Discussionmentioning
confidence: 86%
“…Although nonrigid registration schemes seem the natural choice for lung analysis, due to the elastic nature of lung tissue, combination schemes that comprised of rigid and nonrigid transforms are recently proposed, considering the trade-off between sufficient accuracy and time efficiency in the clinical environment. 12 Registration schemes evaluated in the present study were initially selected on the basis of artificially warped ground truth follow-up data, generated from original baseline images of ten clinical volumetric CT scans, in order to avoid T IV. Average distance error (mean ± standard deviation) of corresponding landmark points in normal lung parenchyma regions and interstitial lung disease affected regions between original baseline and follow-up data registered by the selected registration schemes, as well as between original baseline and unregistered follow-up data.…”
Section: Discussionmentioning
confidence: 99%
“…Although nonrigid transformation models seem the natural choice for lung field registration due to the elastic nature of the lung tissue, combinations of rigid and nonrigid transformation models were also included, as recently reported in the lung CT registration literature. 12 The B-spline grid-spacing applied was 3 × 3 × 3 voxels (approximately 13.2 cm 3 ). Finally, four different gradient descent optimizers were considered (standard gradient decent-SGD, regular step gradient decent-RSGD, adaptive stochastic gradient decent-ASGD, and finite difference gradient decent-FDGD).…”
Section: C Registration Parametersmentioning
confidence: 99%
See 1 more Smart Citation